Should breast cancer survivors be excluded from, or invited to, organised mammography screening programmes? - Bucchi Lauro (BMC, 2011)
Abstract Background The prevalence of breast cancer in developed countries has steadily risen over recent decades. Immediate and long-term health needs of patients, including preventive care and screening services, are receiving increasing attention. A question still unresolved is whether breast cancer survivors should receive mammographic surveillance in the clinical or screening setting and, thus, whether they should be excluded from, or invited to, organised mammography screening programmes. The objective of this article is to discuss the many contradictory aspects of this matter. Discussion Problems with mammographic surveillance of breast cancer survivors include: weak evidence of a reduction in mortality; lack of evidence in favour of one setting or the other; lack of evidence-based guidelines for the frequency and duration of surveillance; disproportionate emphasis placed on the first few years post-treatment, probably dictated by surgical and oncological priorities; a variety of screening policies, as these women are permanently or temporarily or partially excluded from many - but not all - organised screening programmes worldwide; an even greater disparity in follow-up protocols used in the clinical setting; a paucity of data on compliance to mammographic surveillance in both settings; and a difficulty in coordinating the roles of health care providers. In the future, the use of mammography in breast cancer survivors will be influenced by the inclusion of women aged > 69 years in organised screening programmes and the implementation of multidisciplinary breast units, and will probably be investigated by research activities on individual risk assessment and risk-tailored screening. In the interim, current problems can be partially alleviated with some technical solutions in screening data recording, patient flows, and care coordination. Summary Mammographic surveillance of breast cancer survivors is situated at the crossroads of numerous different specialist areas of breast cancer control and management. The solutions for current problems probably lie in some important modifications in the conventional screening procedure that are underway or under study. These developments appear to be directed towards a partial modification of the screening rationale, with an adaptation to meet the diversified breast care needs of women. The complexity of the matter constitutes a call to action for several entities to eliminate the barriers to effective research in this field.